Helminth Glycans at the Host-Parasite Interface and Their Potential for Developing Novel Therapeutics - Bunte, Myrna J. M.; Schots, Arjen; Kammenga, Jan E.; Wilbers, Ruud H. P. (Frontiers in Molecular Biosciences, 2022)
Helminths are parasitic worms that have successfully co-evolved with their host immune system to sustain long-term infections. Their successful parasitism is mainly facilitated by modulation of the host immune system via the release of excretory-secretory (ES) products covered with glycan motifs such as Lewis X, fucosylated LDN, phosphorylcholine and tyvelose. Evidence is accumulating that these glycans play key roles in different aspects of helminth infection including interactions with immune cells for recognition and evasion of host defenses. Moreover, antigenic properties of glycans can be exploited for improving the efficacy of anti-helminthic vaccines. Here, we illustrate that glycans have the potential to open new avenues for the development of novel biopharmaceuticals and effective vaccines based on helminth glycoproteins.